ANALISIS PEMASARAN EMPING MELINJO DI KABUPATEN KLATEN - Agus Editio Wibowo; Ignatius Suprih Sudrajat (Fakultas Pertanian UST, 2018)
This research aims to determine the factors that affect the marketing margin of emping melinjo. This research was conducted in District Jatinom, Manisrenggo, Ngawen and Jogonalan Klaten Regency in February - March 2017. The basic method of research used in this study is the method of observation and survey by conducting direct interviews to respondents using questioner, then collect and compile data, Analyze and explain. The method of determining the location of the research was done purposively, while the respondents were random sampling and the merchant samples were snowball. The results showed the margin of marketing channel 1 Rp. 0, -. marketing channel II Rp.8.250, - marketing channel III Rp.6.500,- marketing channels IV Rp.10.750, -. Factors of sales volume, producer price, consumer price level, packaging cost, transportation cost and number of marketing institutions simultaneously have a significant effect on marketing margin of emping melinjo. Partially sales volume, producer price, consumer price, packaging cost, transportation cost having real effect, while the number of marketing institution has no significant effect.